On the Econometric Analysis of Production When There Are No Output Data - Erik Mellander; Bengt-Christer Ysander (The Research Institute of Industrial Economics (IUI), 1989)
A general method is described which allows a production activity to be analyzed by means of input data only. According to duality theory, the input cost shares can be completely specified without any information about output if the technology is homothetic. It is demonstrated that these cost shares can yield information about elasticities of substitution and factor demand and on productivity development. Moreover, the system of share equations can be generalized to allow for technical and allocative inefficiency and the effects of these inefficiencies on total costs and input demands can be estimated.
Keywords: C81; D22; 330; Production measures; elasticity of substitution; inefficiency; estimation method